Men at home: Imagining liberation in colonial and postcolonial India - Pandey, Gyanendra (Durham and London Duke University Press, 2025)
In Men at Home, Gyanendra Pandey offers a detailed exploration of men$1 (Bs comportment and conduct in the home and the implications of their ambiguous commitment to this critical part of their lives. The author draws on a wealth of archival materials$1 (Bautobiographies, memoirs, fiction, and ethnographies$1 (Bto situate Indian men firmly in the domestic world, underlining their dependence on the family and home. He investigates how men negotiate marriage, intimacy, and conjugality and focuses the effects of the humiliating and constant assertion of gender, caste, and class power in familial interactions. To uncover the nuances of these relationships, Pandey attends to the domestic commitments of upper-, middle-, and lower-class men across religion and caste. s
Keywords: Sociology; Social Sciences; Culture